Effects of C4H9NH3Br additive on properties of CH3NH3PbBr3 perovskite thin films. (1st September 2020) - Yang, Yanchun; Yu, Sheng; Cao, Yongjun; Li, Wei
Abstract : Short‐chain C4 H9 NH3 Br compound can be used as the surface capping to synthesise CH3 NH3 PbBr3 perovskite nanocrystal. In this work, employed as the surface ligand of CH3 NH3 PbBr3 perovskite thin films, the influence of C4 H9 NH3 Br additive on the morphology and optical properties of CH3 NH3 PbBr3 thin films were studied systematically. As the doping ratio of C4 H9 NH3 Br compound increases, the growth of CH3 NH3 PbBr3 crystal grain can be controlled, and optical properties of CH3 NH3 PbBr3 thin films can be improved. The best quality can be obtained with 20% of C4 H9 NH3 Br. Finally, the optimal sintering conditions of CH3 NH3 PbBr3 perovskite thin films are determined at 80°C, 4 min.